Conches in Early Christian Art: Borders of Spatial Perception - Medennikova, Aleksandra E. (Actual Problems of Theory and History of Art, 2019)
Visualization of architecture becomes widespread and gains new meanings in the Late Antiquity. Since the most important category for the architecture is space, its representation in different types of art on plain or slightly curved surfaces could be a problematic artistic task. The most difficult architectural element for the representation is a conch. A space marked with a conch is always connected with an apse or a niche. There presented architecture in the visual arts serves as a frame for narrative scenes or personages. Nevertheless, the spatial value and significance of these forms could be retained. Two certain iconographic motives — shell and canopy — allow us to identify the visualized conch among different other images. They appear in two contexts.The first one is a niche that is more common in sculpture, like sarcophagus of Iunius Bassus and Traditio legis sarcophagus from Arles, or in mosaic decoration, as in the so-called Mausoleum of Galla Placidia. Another element is a tympanum where motives of shell and canopy are purely symbolic, like in Neon Baptistery, or form a complicated spatial system, like in the Hypogeum of via Dino Compagni in Rome. After the analysis of different works of art we can conclude that the visualizing of conches was very importantat that time because they indicated a sacral space and emphasized the importance of characters orobjects disposed beneath.